Rice Yield and Nitrogen Use Efficiency With System of Rice Intensification and Conventional Management Practices in Mkindo Irrigation Scheme, Tanzania - Mboyerwa, Primitiva Andrea; Kibret, Kibebew; Mtakwa, Peter; Aschalew, Abebe (Frontiers in Sustainable Food Systems, 2022)
Abstract Aim This study investigated the impacts of system of rice intensification (SRI) versus conventional management practices (CP) with nitrogen application on rice growth, grain yield, and nitrogen use-efficiency. Methods Field experiments were conducted in wet and dry season, each season the experiment was set in a split-plot randomized complete block design in triplicate with crop management practices in main plots and nitrogen levels in sub-plots. Results The average grain yield in SRI was 7.1 and 6.7; t ha-1 while in CP was 6.1 and 4.4 t ha-1 during wet and dry seasons, respectively. Grain yield of SRI practices was significantly (p<0.05) greater than that of conventional practice (CP) at all levels of nitrogen application. Nitrogen application levels, average yield under SRI management increased by 13.1% in the wet season and 35.8 % during the dry season. Roots under SRI plants had significantly (P< 0.05) greater fresh weight, length, and volume as indicated by increased root dry weight per hill. SRI improved crop growth, effective tillers, filled grains per panicle, grains filling rate, panicle weight, spikelet per panicle, straw yield, and 1000-grain weight. The nitrogen application rate had a significant effect (P< 0.05) on agronomic nitrogen use efficiency (ANUE). As the N application rate increased beyond 90 kg N ha-1, the ANUE and partial factor productivity (PFP) under both SRI and CP significantly decreased in both seasons. Conclusion Overall, SRI production system with 60 kg N ha−1 improved rice growth and yield hence improved nitrogen use efficiency compared to conventional practice.